Pengaruh Model Pembelajaran Discovery Learning terhadap Hasil Belajar IPS SMP Negeri 3 Medan - Binnner Sihaloho; Lusiana Simamora (Journal on Education, 2023)
This study aims to determine the effect of student learning outcomes in the treatment of the Discovery Learning learning model; To determine the interaction of learning models on learning outcomes. This research is classified as quasi-experimental research. This research will be conducted at SMP Negeri 3 Medan. The population in this study were all class VII students of SMP Negeri 3 Medan for the 2022/2023 academic year. From the results of the research findings it was found that for social science learning outcomes to learning models a significant value was obtained for learning outcomes to learning models 0.003 <0.05, and for social science learning outcomes based on learning interest with teaching classes had sig. 0.027 <0.05 which means there is an interaction between the two. This means that there is an interaction with the Discovery Learning learning model that affects learning outcomes.